PERBEDAAN KADAR TRIGLISERIDA PADA PENGKONSUMSI KOPI DAN BUKAN PENGKONSUMSI KOPI - Kahar, Hartono (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PERBEDAAN KADAR TRIGLISERIDA PADA PENGKONSUMSI KOPI DAN BUKAN PENGKONSUMSI KOPI Dr. dr. Hartono Kahar, Sp.PK. MQIH. Prodi D3 Analis Kesehatan UM Surabaya AbstractCoffee is a beverage that is loved by the people of Indonesia. Coffee can increase LDL and triglycerides (Royyak, 2010). Triglycerides are a type of lipid (fat) found in the blood. When we eat, our bodies change partially unused calories into triglycerides. Triglycerides are stored in the fat cells of the body, if stored too long will be cholesterol and accumulate in the blood vessels, causing constriction of blood vessels and increase the risk of heart attack. Formulation of the problem in this study is Are there differences in the levels of triglycerides in coffee drinkers and non-coffee drinkers ?. The purpose of this study to determine differences in triglyceride levels in coffee drinkers and non-coffee drinkers. Type of research is observational with a total sample of 30 samples. 15 samples for coffee drinkers and 15 samples for non-coffee drinkers. Samples are healthy people who are accustomed to consuming coffee and rarely consume coffee every day. Types of coffee are consumed coffee mashed. The results showed average levels of triglycerides in the coffee drinkers of 245 mg / dl and the average levels of triglycerides in non-coffee drinkers of 113.33 mg / dl. Statistical analysis using the t-test showed that the levels of triglycerides free at coffee drinkers was higher than non-coffee drinkers. Keyword : coffea, LDL